Influência de fatores físicos no padrão fluvial e setorização da bacia do cura malal grande (Argentina) - Ortuño Cano, María de Los Ángeles (2022)
The characterization of a basin is the starting point for research to generate a global idea about the functioning of a river system. The set of physical-natural characteristics are elementary in the description of the hydric dynamics together with the delimitation and sectorization of the hydrographic basins. The objective of this work is to analyze the structural, lithological, hypsometric and slope factors of the Cura Malal Grande basin (Argentina) and their influence on its sectorization and the structuring of its drainage network as an input for the study of its hydrographic dynamics. The basin is characterized by significant differences in elevation and slope. On the distal sector, the structural factors are the determinants to define the middle and lower basin. The types of fluvial pattern and a transitional zone between both of them were associated with the identified sectors of the basin.